PERSPEKTIF BUDAYA INDONESIA DAN TIMOR LESTE OLEH MAHASISWA BIPA TIMOR LESTE DI UNIVERSITAS ISLAM MALANG - Septian, Mohammad Imam Ghozali Fajar (Universitas Islam Malang, 2025)
Abstract: Indonesian Language for Foreign Speakers (BIPA) is growing with the declaration of Indonesian as one of UNESCO's official languages. Development in Southeast Asia is also accelerating, especially in Timor-Leste. Timor Leste has strong ties with Indonesia. This study aims to describe the perspectives of East Timorese BIPA students on Indonesian culture who follow the BIPA programme at the Islamic University of Malang. This research used descriptive qualitative method with data collection techniques through observation, interview and mini-project documentation study. The research subjects were 19 BIPA students at advanced level. The result of the research was to explain the positive perspective of BIPA students towards Indonesian culture. Positive perspectives in several areas, namely BIPA learning, Indonesian education, Indonesian weddings, traditional musical instruments, spiritual culture and bilateral economic relations. This research provides a broader perspective and increased effectiveness in cultural learning in BIPA.